2008
DOI: 10.1186/1475-2875-7-127
|View full text |Cite
|
Sign up to set email alerts
|

Amodiaquine-artesunate vs artemether-lumefantrine for uncomplicated malaria in Ghanaian children: a randomized efficacy and safety trial with one year follow-up

Abstract: Background: Artesunate-amodiaquine (AS+AQ) and artemether-lumefantrine (AM-L) are efficacious artemisinin combination therapy (ACT) regimens that have been widely adopted in sub-Saharan Africa. However, there is little information on the efficacy of these regimens on subsequent episodes beyond 28 days, or on the safety of repeated treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
72
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 46 publications
15
72
1
Order By: Relevance
“…The results showed a high cure rate for both regimens after a standard 28-day follow-up. These results are consistent with efficacy results reported from several sub-Saharan African countries, [34][35][36] indicating a high overall cure rate with these regimens in the short term (28-day). Therefore, the data are in line with studies conducted in Ghanaian children showing lower parasitological and clinical failure rates in the ASAQ compared with the AL arm.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed a high cure rate for both regimens after a standard 28-day follow-up. These results are consistent with efficacy results reported from several sub-Saharan African countries, [34][35][36] indicating a high overall cure rate with these regimens in the short term (28-day). Therefore, the data are in line with studies conducted in Ghanaian children showing lower parasitological and clinical failure rates in the ASAQ compared with the AL arm.…”
Section: Discussionsupporting
confidence: 91%
“…However, if one considers all patients and observations, we cannot quantitate the changes in a manner that is easily transposed into net gains or losses. Regarding direction of changes, there was a net decrease in leukocyte counts resulting from a decrease in neutrophil counts (also reported by Adjei and others 1 ) that was proportionally greater than the increase in lymphocyte counts. Hemoglobin levels and platelet counts also increased.…”
Section: Discussionsupporting
confidence: 65%
“…1 Except for anemia, little is known about children in Africa with P. falciparum malaria; other hematologic parameters pre-antimalarial and post-antimalarial treatments have not been studied (or at least reported) systematically for this population. Most of the (limited) data available from the existing literature concerns adult malaria patients from areas of low malaria endemicity.…”
Section: Introductionmentioning
confidence: 99%
“…The full details of the trial have been reported previously elsewhere 7 . Briefly, children with uncomplicated malaria fulfilling inclusion and exclusion criteria of the trial were randomized to treatment with artesunate+amodiaquine, artemether-lumefantrine, or amodiaquine monotherapy and then followed up, initially for 28 days, and then monthly for up to one year.…”
Section: Methodsmentioning
confidence: 99%